Case reports article - Rapidly growing mass in the ear canal: A rare case of isolated superficial angiomyxoma - Arepen S.A.M.; Hassan N.E.; Rani A.A.; Hitam S.; Daud M.K.M. (Universiti Sains Islam Malaysia, 2024)
Indexed by Scopus/ERA